The Effectiveness of Group Spiritual-Islamic Mindfulness on Compassion Fatigue, Empathy and Optimism in Nurses - Gholamhosin Asgari; Mahin Etemadinia; Farnaz Farshbaf Manisefat (روانشناسی و روانپزشکی شناخت)
Introduction: During their working process nurses are involved in extensive tensions which cause an increase in compassion fatigue and a decrease in empathy and optimism which has a negative effect on the quality of their clinical services. Aim: This research was conducted with the aim of determining the effectiveness of group spiritual-Islamic mindfulness on nurses’ compassion fatigue, empathy and optimism. Method: This research was a semi-experimental study whose statistical population included nurses working in Arefian Hospital in Urmia city. In the year 1401, 60 nurses were selected randomly using available sampling method and were put into two experimental and control groups (30 people in each group). The experimental group received inervention during 8 sessions of 90 minutes, and the control group did not receive any intervention. The measurement tools were questionnaires from Figley's Compassion Fatigue (1995), Baron-Cohen's Empathy (2003) and Seligman’s Pessimism-Optimism (1982). The participants completed the questionnaires in the pre-test, post-test and follow-up phases. The data was analyzed using the repeated measures and SPSS22 software. Results: There was a significant difference between the pre-test and post-test scores in the experimental and control groups in all three research variables. The intervention of group spiritual-Islamic mindfulness had a significant effect on nurses’ compassion fatigue (F‌=‌10.980; P‌<‌0.01), empathy (F‌=‌53.071; P‌<‌0.01) and optimism (F‌=‌25.406; P‌<‌0.01). Conclusion: Group spiritual-Islamic mindfulness was effective on nurses' compassion fatigue, empathy, and optimism; Therefore, this intervention can be used to improve the performance and quality of clinical care of nurses.